1994
DOI: 10.1007/bf00285454
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Phytophthora infestans ipiB and ipi0 genes in planta and in vitro

Abstract: The ipiB and ipiO genes of the potato late blight fungus Phytophthora infestans (Mont.) de Bary were isolated from a genomic library in a screen for genes induced in planta. Expression of these genes was studied during pathogenesis on various host tissues and different host plants, some of which show specific resistance against P. infestans infection. During pathogenesis on leaves and tubers of the fully susceptible potato cultivar (cv.) Ajax and on leaves of the fully susceptible tomato cv. Moneymaker, the P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 30 publications
0
40
0
1
Order By: Relevance
“…The electrophoresis buffer and blotting buffer consisted of 10 and 25 mM sodium phosphate, pH 7.0, respectively. RNA gel blots were hybridized and washed as described previously (Pieterse et al, 1994) and exposed to X-Omat or Biomax films. DNA probes were labeled with [a-32 P]dCTP by random primer labeling according to the manufacturer's instructions (Promega).…”
Section: Rna Gel Blot Analysismentioning
confidence: 99%
“…The electrophoresis buffer and blotting buffer consisted of 10 and 25 mM sodium phosphate, pH 7.0, respectively. RNA gel blots were hybridized and washed as described previously (Pieterse et al, 1994) and exposed to X-Omat or Biomax films. DNA probes were labeled with [a-32 P]dCTP by random primer labeling according to the manufacturer's instructions (Promega).…”
Section: Rna Gel Blot Analysismentioning
confidence: 99%
“…For RNA gel blot analysis, 15 g of total RNA was electrophoretically separated on denaturing formaldehyde-agarose gels and blotted onto Hybond-N ϩ membranes (Amersham, 's-Hertogenbosch, The Netherlands) by capillary transfer, as described by Sambrook et al (1989). RNA gel blots were hybridized and washed as described previously (Pieterse et al, 1994) and exposed to a Kodak X-OMAT AR film. DNA probes were labeled with ␣-32 P-dCTP by random primer labeling (Feinberg and Vogelstein, 1983).…”
Section: Rna Gel Blot Analysismentioning
confidence: 99%
“…For the Cladosporium fulvum Avr9 gene and a number of other plant-induced genes in fungi, it has been demonstrated that expression can also be increased under conditions of nitrogen and/or carbon deprivation (9,30,40,43). In contrast, the mig1 gene was not induced under the starvation conditions tested.…”
Section: Discussionmentioning
confidence: 99%